Potential Development Students and the Community Integrated by Al Baghdadi Islamic Boarding School, Karawang Regency - Iqbal Jamalulail; Sari Viciawati Machdum (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The research objectives are as follows: 1. To describe and explain the development of students at the Albaghdadi Islamic Boarding School in order to increase the potential of the community (Internal), 2. To explain the stages and steps of the Albaghdadi Islamic Boarding School in increasing the community's potential (External). 3. Explaining the outcome of increasing the potential of students and the community. The method used in this study is a qualitative type with a phenomenological approach, this research was carried out at the Albaghdadi Islamic Boarding School on Proklamasi Street, Sasak Hamlet, Amandari Village, Rengasdengklok District, Karawang Regency, and West Java. As for data analysis with the following steps: 1) Open Codding , 2) Axial Codding 3) Selective Coding The results showed that the Al Baghdadi Islamic Boarding School in developing the potential of students and the community, first, the Al Baghdadi Islamic Boarding School carried out the development of santri and community resources both in terms of skills, Islamic religious scholarship, entrepreneurship (internal), second, the Al Baghdadi Islamic Boarding School carried out the following stages: are constructive and persuasive starting from preparation, social mapping, program planning, implementation, and evaluation where this stage is carried out continuously, thirdly , Pesantren Al Baghdadi makes improvements to the community both in terms of skills, entrepreneurship, finance, and spirituality. The guidance carried out by the Al Baghdadi Islamic Boarding School for students and the surrounding community has several aspects: significant continuity. This can be seen from the observations that the community and the pesantren are united. Society has dependence on pesantren, and vice versa